Spanish Adaptation of the “Five-Factor Narcissism Inventory-Short Form” (Ffni-Sf) in Venezuelan University Students - Chaustre Jota, Daniel Alberto (2021)
Narcissism is a personality construct that has numerous measuring instruments; even though a multidimensional approach has been proposed, the majority of these instruments are one-dimensional measures. Recently, one of the few measures that captures simultaneously multiple traits of narcissism and its two mayor general expressions: vulnerable narcissism and grandiose narcissism, is the Five-Factor Narcissism Inventory (FFNI). Even with the growing research that uses this inventory, Spanish speaking populations do not count with an adaptation to their language. For this reason, a Spanish adaptation of the FFNI in its 60-item short form (FFNI-SF) was assessed, with its corresponding psychometric analysis included. Once translated, through a “snowball” method, the inventory was administrated via online. The final sample consisted in a total of 156 students from a private university, from which 82% were women and the rest were men. The inventory showed adequate reliability indexes, in the majority of dimensions; also, in regard to the validity of the measures, sex and age showed significant correlations with different dimensions of the inventory, as stated in the literature. This Spanish version of the FFNI-SF showed adequate psychometric properties in the study sample, so it may be applied in future studies with Spanish speaking samples, in order to test its adequacy in different countries and also expand upon the knowledge about narcissism.